A deadly deletion - Barrett, Lorna (Barrett, Lorna. Booktown mystery., 2022)
Tricia has just received a second marriage proposal within fifteen minutes. The first was from her friend with benefits, Marshall Chambers, and the second from her ex-lover, police chief Grant Baker. Tricia's got some serious thinking to do. She's still weighing her options when she hears the sound of an engine roaring down Main Street. It's a big white pickup truck that aims for and hits Marshall as he's walking back to his apartment. Tragically, he's killed, leaving Tricia feeling bereft and guilty. She retreats to the apartment of her sister, Angelica, to wait for Baker to update her on what happened. While there, Tricia takes Angelica's dog out for a comfort call behind the building, and the same white pickup roars up the alley and just misses hitting Tricia. Still shaken, Tricia returns to her mystery bookshop, Haven't Got a Clue, and is met by federal marshal Kirby, who tells her that Marshall had been in the Federal Witness Protection Program. Everything Marshall told Tricia was a lie--in particular, that he was a widower. Was his death an act of revenge? Tricia must find this deadly driver before she becomes the next victim.